PENGARUH KETIDAKBERATURAN STRUKTUR TERHADAP SINGLE SYSTEM DAN DUAL SYSTEM - Syafrizal Syafrizal; Alex Kurniawandy; Muhammad Yusa (Racic : Rab Construction Research, 2025)
Earthquakes are vibrations caused by the movement of tectonic plates and volcanic activity, earthquakes that occur due to the activity of tectonic plate movements are earthquakes that cause great damage and casualties. This massive damage and loss of life occurred as a result of being crushed by the debris of buildings that collapsed due to vibrations caused by the movement of tectonic plates, Existing buildings are currently designed not to follow earthquake-resistant building standards that refer to SNI 1726: 2019. SNI 1726: 2019 there are several criteria for earthquake resistant buildings, namely the influence of the P-Delta effect, horizontal irregularities in the structure and vertical irregularities in the structure, there are two types of structures that are commonly used, namely Single System and Dual System. Single System is a Moment Bearing Frame Structure (SRPM), This type of earthquake load on the building will be carried by the columns and beams, Dual System is a Moment Bearing Frame Structure (SRPM) and Structural Wall Structure (SDS), This type combines columns, beams and shear walls as the structure to carry the earthquake loads that occur in the building. The research aims to analyze the effect of structural irregularities on Single System and Dual System structures and the level of structural performance, the results obtained Single System and Dual System structures experience several horizontal and vertical irregularities in the structure such as torsion irregularities, inner angle irregularities, weight (mass) irregularities, weak level irregularities due to discontinuities in the lateral strength level and the level of performance of Single System structures at Damage Control and Dual System at Immediate Occupancy.